Interaksi Asupan Magnesium Harian pada Kram yang Dialami oleh Atlet Hand Ball: Penelitian - Herianto; Eka Supriatna; Uray Gustian (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Cramps are a problem that athletes can experience, and this condition is commonly associated with various factors such as insufficient warm-up and stretching. Therefore, this research was conducted to examine the adequacy of magnesium from the perspective of the daily magnesium intake of athletes. The research sample consists of 14 athletes from the Pontianak City Handball Club, including 7 female and 7 male athletes. Data collection will be done using food recall questionnaires, activity recall questionnaires, and questionnaires about cramp occurrences in athletes. The data was analyzed using the Nutrisurvey application, and then the percentage of daily adequacy was calculated. The research results show that 92.86% of athletes have sufficient magnesium levels, while 7.14% are deficient. Regarding cramps experienced by athletes, 71.43% did not experience cramps, and 28.57% did. The research found that even athletes with sufficient daily magnesium levels still experienced cramps. In conclusion, even with sufficient daily magnesium intake, it cannot guaranty that the body will be free from injury and cramping issues.